Interaction of genotype and fertilization on phosphorous uptake efficiency in rice under acid soil - Taki, Oyem; Thakuria, Dwipendra (Umiam ; CPGS-AS, CAU, 2021)
In the anticipated scenario of potential phosphate crisis by 2050 and the ever-increasing world food demand, there is urgent need for improving phosphorus (P) use efficiency (PUE) in crop production especially in acid soil regions. From plant breeding point of view, the quantitative trait loci (QTL) Pup1 is considered one of the most favorable QTLs for the development of rice (Oryza sativa L.) varieties tolerant to P deficient soils (Chin et al., 2011). Further, the rhizosphere based nutrient management approach like seedling root-dip treatment in P amended soil slurry along with phosphate solubilizing biofertilizer is known to enhance rice yield and PUE in strongly acid soils (Kalidas-Singh and Thakuria, 2018).So this study assessed whether the improved lines and HYVs of rice exhibit variable P uptake efficiency (PUpE) depending on the presence or absence of QTL Pup1 containing PsTol1 gene. Besides, the choice of nutrient management options may increase the effect of P efficient rice genotype in terms of PUpE in strongly acid soils. To test the above hypotheses, a mesocosm pot experiment and a field experiment was lead in strongly acid soil. Altogether, 12 rice genotypes [Improved lines (CAUS-103, CAUS-105, CAUS-107,CAUS-110 and CAUS-122), Landrace (Chakhao poireiton, Mang meikri, Kala joha)and HYV (Sahbhagi dhan, CAU-R1, Shahsarang, Kasalath) among which CAUS-103, CAUS-105, CAUS-122, Kasalath and Sahbhagi dhan are QTL Pup1+] were grown in pots maintaining 5 replications. The recommended doses of urea and muriate of potash were applied (60-40as N-K2O kg ha-1) and experiment was maintained till 45 days after transplanting (DAT). In field experiment, 4 efficient rice genotypes (Pup1+, CAUS-103, CAUS-105 and CAUS-122; Pup1- CAUS-110) were selected and were grown under 3 fertilization regimes: FR1, 100 % RDF (NP2O5 -K2O at 60-40-40 kg ha-1) + Zn as foliar spray@ 0.5 %; FR2, 50 % RDF + Seedling root dip in SSP soil slurry @ 112.5 mg P kg-1 soil for 10 h (overnight) + CAU Bioenhancer (2.5 kg ha-1) + Zn as foliar spray (0.5%); and FR3, SSP soil slurry seedling root dip @ 112.5 mg P kg-1 soil for 10 h (overnight) + CAU Bioenhancer (2.5 kg ha-1) +Zn as foliar spray (0.5%). In the pot experiment at seedling stage (21 DAS) the high yielding varieties (HYV) like CAU-R1, Kasalath (Pup1+) and Sahbhagi dhan (Pup1+) gave longer root length than shoot length (P FR1 > FR3 and CAUS-105 (Pup1+) > CAUS-103 (Pup1+) > CAUS-110 (Pup1- ) > CAUS-122 (Pup1+). At the time of harvest soil available P2O5 was seen higher in plot treated with FR2 followed by FR1. FR2 also showed the lowest readily soluble Al irrespective of genotype while FR1 gave the highest. Highest soil available Fe was observed in FR1 while the lowest soil available Mn was found FR3. In comparison to Pup1- rice genotype, Pup1+ rice genotype showed better P uptake and higher yield in response to fertilization regimes and under P deficient acid Inceptisol. Among improved lines CAUS-105 and CAUS-103 are promising in terms of grain yield. Besides, FR2 maintained higher nutrient content and yield by better synchronization of soil available P with the critical growth stages of crop.
Keywords: Rice -- Acid soils; Rice -- Fertilization -- Phosphorous; Rice -- Nutrient management